1985
DOI: 10.1111/j.1399-0039.1985.tb00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Class II antigens on canine T lymphocytes

Abstract: A panel of crossreactive anti‐human, ‐mouse and ‐rat MHC class II monoclonal antibodies (Mabs) was used to examine MHC class II antigen expression on canine T lymphocytes by cytofluorometry. The presence of MHC class II antigens was demonstrated on activated T lymphoblasts as well as on non‐stimulated peripheral blood T lymphocytes. A number of anti‐MHC class II Mabs reacted only with activated T lymphoblasts. Immunoprecipitation studies confirmed the Ia‐like or MHC class II molecular character of the antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 38 publications
(16 reference statements)
2
7
0
Order By: Relevance
“…3 and 4). Our finding is consistent with previous studies that showed more than 90% of bottlenose dolphins’ [35] and beluga whales’ [36] peripheral blood cells within lymphocyte region express MHC class II, which is also observed in ungulates and carnivores such as swine [36], equine [37], canine [38], and feline [39]. Although, MHC class I is displayed on all human and mouse nucleated cells, we found that only a small percentage of dolphin cells expressed MHC class I (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…3 and 4). Our finding is consistent with previous studies that showed more than 90% of bottlenose dolphins’ [35] and beluga whales’ [36] peripheral blood cells within lymphocyte region express MHC class II, which is also observed in ungulates and carnivores such as swine [36], equine [37], canine [38], and feline [39]. Although, MHC class I is displayed on all human and mouse nucleated cells, we found that only a small percentage of dolphin cells expressed MHC class I (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The pattern of reactivity of 2D16 with B and T lymphocytes of rhesus macaques and sheep, and human lymphoid cell lines is in accord with the expected distribution of class I1 antigens on lymphocytes of man, mouse and bovine (Nadler et al 1981, Hammerling et al 1979, Spooner & Ferrone 1984, Lewin et al 1985 and is different from that found on lymphocytes of swine and dogs in that the majority of peripheral blood T lymphocytes as well as B lymphocytes express class I1 antigens in the latter species (Thistlewaite et al 1983, Deeg et al 1982, Iwaki et al 1983, Doveren et al 1985. In the case of the dog, it has not been emphasized that the level of expression of class I1 antigens on T lymphocytes is less than that on B lymphocytes; this was indicated by immunohistochemical staining of canine lymphoid tissues with 2D16, CIA and TH21A in this study.…”
Section: Discussionsupporting
confidence: 51%
“…The possibility of diffusion of reaction product from intensely stained adjacent non-lymphoid cells could not be excluded as an explanation of this phenomenom. However, a subpopulation of class I1 antigen bearing thymocytes has been described in mouse, man and dog (Krammer et al 1975, Williams et al 1980, Doveren et al 1985, hence it is possible that the staining reactions are a true indication of class I1 antigen expression. We were unable to unequivocally determine the identity of the intensely stained non-lymphoid cells in the thymic medulla with our single labeling technique.…”
Section: Discussionmentioning
confidence: 99%
“…Eight functional genes and five pseudogenes have been identified to date for the class I and II regions. In particular, MHC class II molecules in the dog are constitutively expressed on the surface of Dendritic cells (DCs), macrophages, B cells, T cells, thymocytes and vascular endothelium (Doveren et al 1985;Mueller et al 2004). DCs and MHC class II molecules play crucial roles in regulating immune responses in skin (Delves and Roitt 2000).…”
Section: Discussionmentioning
confidence: 98%